Assessment of cadmium concentration in predominant Indian linseed cultivars: Assessment of cadmium concentration in predominant Indian linseed cultivars - A AZIZ QURESHI; A L RATHNAKUMAR; DIVYA AMBATI; CH V HARIPRIYA; M SUJATHA (Journal of Oilseeds Research, 2023)
Humans require consuming low quantities of cadmium (Cd), a non-nutritive and potentially toxic heavy metal, primarily via the dietary intake of grains. An analysis was conducted to investigate concentration of Cd content in 10 predominant linseed (Flaxseed) cultivars available at ICAR-IIOR. The objective of study was to provide information that will assist in the breeding of low Cd-accumulating linseed cultivars. Hence, efforts were made to identify varietal differences in the uptake of Cd in various seeds among 10 linseed cultivars grown in India in natural environment. The cadmium concentration in Indian cultivars ranged from 0.85 to 1.05mg/kg. Minimum Cd was noticed in cultivar BRLS and highest in Shekhar